1997
DOI: 10.1007/s11746-997-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of composition on the performance of sodium linear alkylbenzenesulfonate (NaLAS)

Abstract: Like other commercial surfactants, commercial linear alkylbenzenesulfonate is not a single compound but a mixture of components. This mixture comprises different carbonchain homologs, different phenyl isomers, and, in addition, the manufacturing co-product, dialkyltetralin sulfonate. Current manufacturing technology makes it possible to easily vary the average carbon chainlength. On the other hand, the phenyl isomer distribution and dialkyltetralin sulfonate content can be changed only within a certain range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…The effect of the phenyl sulfonate group position on solubility in this study is consistent with previously reported results ascribed to a branched alkyl chain and to a centrally located hydrophilic group (10)(11)(12). For commercial-grade LAS, similar results have been reported by Smith (4).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The effect of the phenyl sulfonate group position on solubility in this study is consistent with previously reported results ascribed to a branched alkyl chain and to a centrally located hydrophilic group (10)(11)(12). For commercial-grade LAS, similar results have been reported by Smith (4).…”
Section: Resultssupporting
confidence: 92%
“…Since the symmetry of C 12 -6-LAS may optimize its inter-and intramolecular hydrophobic interactions, compared to C 12 -5-LAS, this presumably may facilitate micellization and result in a slight reduction in CMC value. This is consistent with the smaller solubility of C 12 -6-LAS compared to C 12 -5-LAS in water, reported by Smith (4). In our work on the molecular interac- tion of mixtures of surfactants, maximum interaction between two surfactants was found for those with the same hydrophobic alkyl chain length (Ref.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…51 As shown in Fig. 1a, commercially available NaLAS contains several isomers and it has been previously shown [52][53][54][55][56] that the position of the benzene group, the length of the alkyl chain and differences in molecular area can impact the slope of g vs. concentration curve at lower concentrations, as well as the its value at CMC g CMC . A previous study 55 indicates that isomers with headgroups positioned close to the centre of the alkyl chain tend towards higher g and CMC values.…”
Section: Soft Matter Papermentioning
confidence: 96%
“…C 12 -2-LAS was spiked from a stock made in methanol, while keeping the amount of solvent in the sediment suspension below 1% of the total volume of the system. C 12 -2-LAS aqueous concentration ranged from 0.02 to 2 mg/L, which are well below the Critical Micelle Concentration (105 mg/L; Smith, 1997). The system was left to equilibrate on a rolling device for 24 h at room temperature (20 AE 1 C).…”
Section: Determination Of the Sorption Coefficientsmentioning
confidence: 99%